JURIDICAL ANALYSIS OF THE IMPLICATIONS OF THE EMPLOYMENT COPYRIGHT LAW ON FOREIGN INVESTMENT IN INDONESIA: ANALISIS YURIDIS IMPLIKASI UNDANG-UNDANG CIPTA KERJA TERHADAP INVESTASI ASING DI INDONESIA - Mifta, Sarah (Jurnal Kajian Ilmu Hukum, 2023)
Investment plays a crucial role in a country's development process, transforming economic potential into real economic power and providing a boost to positive economic growth. The demand for foreign investment has prompted many countries to implement changes in their legal systems. One of these changes is commercial law reform, which aims to attract foreign investment. Indonesia has taken a breakthrough through Law Number 6 of 2023 on Job Creation (Job Creation Law) by implementing an Omnibus Law approach. More than 80 laws and more than 1200 articles have been revised simultaneously into one legal document, namely the Job Creation Law that regulates various sectors in 11 groups. The type of research conducted by researchers is normative juridical research, which involves the study of library materials and secondary data, including primary, secondary, and tertiary legal materials. The government has endeavored to create basic investment policies that support a conducive national business climate. Nevertheless, the reality is that many investors are still reluctant to invest in Indonesia due to difficulties in business licensing. The commitment to improve the investment climate is also reflected in Part III of the Job Creation Law that regulates the Improvement of Investment Ecosystem and Business Activities. Meanwhile, efforts to facilitate business actors in investing are seen in Section VI of the Job Creation Law Investasi memegang peran krusial dalam proses pembangunan suatu negara, mengubah potensi ekonomi menjadi kekuatan ekonomi yang nyata dan memberikan dorongan terhadap pertumbuhan ekonomi yang positif. Tuntutan akan investasi asing mendorong berbagai negara untuk mengimplementasikan perubahan dalam sistem hukum. Salah satu bentuk perubahan ini adalah reformasi hukum komersial, yang bertujuan untuk menarik minat investasi asing. Indonesia telah mengambil terobosan maju melalui Undang-Undang Nomor 6 Tahun 2023 tentang Cipta Kerja (UU Cipta Kerja) dengan menerapkan pendekatan Omnibus Law. Lebih dari 80 undang-undang dan lebih dari 1200 pasal telah direvisi secara bersamaan menjadi satu dokumen hukum, yaitu Undang-Undang Cipta Kerja yang mengatur berbagai sektor dalam 11 kelompok. Jenis penelitian yang dilakukan oleh peneliti adalah penelitian yuridis normatif, yang melibatkan kajian bahan pustaka dan data sekunder, termasuk bahan hukum primer, sekunder, dan tersier Pemerintah telah berupaya untuk menciptakan kebijakan dasar penanaman modal yang mendukung iklim usaha nasional yang kondusif. Meskipun demikian, kenyataannya masih banyak investor yang enggan berinvestasi di Indonesia karena kesulitan dalam perizinan berusaha. Komitmen untuk memperbaiki iklim investasi juga tercermin dalam Bagian III UU Cipta Kerja yang mengatur Peningkatan Ekosistem Investasi dan Kegiatan Usaha. Sementara itu, upaya untuk memfasilitasi pelaku usaha dalam berinvestasi terlihat dalam Bagian VI UU Cipta Kerja.